Measuring Public Reaction to Violence Against Doctors in China: Interrupted Time Series Analysis of Media Reports - Yang, Qian; Tai-Seale, Ming; Liu, Stephanie; Shen, Yi; Zhang, Xiaobin; Xiao, Xiaohua; Zhang, Kejun (JMIR Publications, 2021)
BackgroundViolence against doctors in China is a serious problem that has attracted attention from both domestic and international media. ObjectiveThis study investigates readers' responses to media reports on violence against doctors to identify attitudes toward perpetrators and physicians and examine if such trends are influenced by national policies. MethodsWe searched 17 Chinese violence against doctors reports in international media sources from 2011 to 2020. We then tracked back the original reports and web crawled the 19,220 comments in China. To ascertain the possible turning point of public opinion, we searched violence against doctors-related policies from Tsinghua University ipolicy database from 2011 to 2020, and found 19 policies enacted by the Chinese central government aimed at alleviating the intense patient-physician relationship. We then conducted a series of interrupted time series analyses to examine the influence of these policies on public sentiment toward violence against doctors over time. ResultsThe interrupted time series analysis (ITSA) showed that the change in public sentiment toward violence against doctors reports was temporally associated with government interventions. The declarations of 10 of the public policies were followed by increases in the proportion of online public opinion in support of doctors (average slope changes of 0.010, P<.05). A decline in the proportion of online public opinion that blamed doctors (average level change of -0.784, P<.05) followed the declaration of 3 policies. ConclusionsThe government's administrative interventions effectively shaped public opinion but only temporarily. Continued public policy interventions are needed to sustain the reduction of hostility toward medical doctors.